Analisis Pengaruh Voucher Diskon dan Kemudahan Penggunaan Aplikasi terhadap Keputusan Pembelian Melalui Aplikasi Grabfood: Studi pada Mahasiswa Jurusan Manajemen FE Unimed - Ricky Louis Naibaho; Sabda Dian Nurani Siahaan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the extent of the influence of the provision of discount vouchers and the ease of use of the application on purchase decisions through the GrabFood service among students of the Management Study Program, Faculty of Economics, State University of Medan. In today's digital era, app-based food delivery services are increasingly in demand due to the ease of access, convenience, and various promotions offered. GrabFood as one of the leading online food service providers in Indonesia utilizes marketing strategies in the form of providing discount vouchers and improving user experience to attract consumer interest. The approach used in this study is a quantitative approach with purposive sampling techniques to determine samples that are relevant to the research objectives. The population in this study is GrabFood application users, with a total of 100 students. Data were collected through questionnaires and processed using SPSS software version 26 to analyze the relationship between independent and bound variables. The results of the analysis show that the discount voucher variable has a positive and significant impact on purchase decisions. Students tend to take advantage of discounts as the main consideration before ordering food. The same applies to the variable of ease of use of the application which also has a positive and significant effect. The user-friendly interface features of the GrabFood application, transaction speed, and practical payment system are important factors in attracting buyers. In addition, simultaneously these two variables have been proven to influence purchasing decisions positively and significantly. This research is expected to provide input for GrabFood management to continue to optimize promotions and application features to further increase consumer satisfaction and loyalty among students.